Clinical and immunological aspects of hyper-IgM syndrome - Ersoy, Fügen; Sanal, Özden; Tezcan, İlhan (The Turkish Journal of Pediatrics, 1990)
Eight patients with Hyper–IgM syndrome were subjected to clinical and immunological evaluation. There were seven males and one female. All the patients had recurrent pyogenic infections; one had lymphoid hyperplasia with centrally necrotic granulomas, and one had gingivitis with neutropenia. Isohemagglutinin titers were either high or normal in all the patients and five had group 0 blood. The percentage of IgM-bearing cells were normal in five patients. The percentage of T cells were normal in all the patients, helper T cells were decreased in two patients, and suppressor T cells were increased in four patients. These results suggest that at least in some patients, the imbalances of T cell subsets may play a role in the pathogenesis of the disease rather than it being attributed to an intrinsic B cell defect.